The Influence of Brand Image, E-Word of Mouth, Impulse Buying and Promotion on Purchasing Decisions at Tiktok Shop - Bela, Ika; Prastyo, Agustin Hari; Kusuma, Dedy Wijaya (MBA : Journal of Management and Business Aplication, 2024)
This study aims to determine the effect of Brand Image, E-Word of Mouth, Impulse Buying and Promotion on Purchasing Decisions at Tiktok Shop (Case Study on Students of the Mandala Jember Institute of Technology and Science) both partially and simultaneously. This type of research is quantitative. The population in this study were students of the Mandala Jember Institute of Technology and Science. The sample used was 100 respondents using the Ferdinand formula. Data analysis techniques using the Classical Assumption Test, Multiple linear regression analysis, Determination Coefficient Test (R2) and Hypothesis Test. The results showed that the Brand Image and Promotion variables partially influenced purchasing decisions at Tiktok Shop, but E-Word of Mouth and Impulse Buying had no partial effect on purchasing decisions at Tiktok Shop.